Cavity leakage flow on annular diffuser cascades based on numerical simulation and self-organizing map algorithm - Fan, Pengwei; Kong, Xiaozhi; Huang, Tianshuo; Liu, Yuxin; Wang, Hong (Physics of fluids (1994), 2025)
To explore in greater depth how the leakage flow from the shrouded stator cavities affects the performance of the aero-engine compressor, a high-load compressor cascade is taken as the research object, and the specific effects of the radial and circumferential momentum of the cavity outlet leakage flow on the performance of the cascade are analyzed by using the method of numerical simulation and the Self-Organizing Map algorithm. The analysis results show that under the condition of 100% design speed, the leakage flow increases the total pressure loss coefficient of the cascade by 4.54% and the energy loss by 4.16%. Under the condition of 80% design speed, these increases rise to 7.36% and 5.47%. The average radial momentum of the leakage flow at the cavity outlet is positively correlated with the total pressure loss and entropy increase loss of the cascade, and the similarities with the entropy increase loss coefficient are greater than 0.8 under the two speed conditions, which indicate highly correlated. The average circumferential momentum of the leakage flow at the cavity outlet is positively correlated with the entropy increase loss and negatively correlated with the total pressure loss of the cascade. Under the condition of 80% design speed, the circumferential momentum of the leakage flow at the cavity outlet has a greater influence on the two performance parameters, and the similarities can reach 0.56 and −0.52, respectively. Moreover, the influence of the cavity leakage flow at different positions of the cavity outlet surface and different momentum on the performance of the cascade are also different, and there can be a contradictory phenomenon where changes in momentum are beneficial for reducing the total pressure loss coefficient but have a negative impact on reducing the energy loss.